2018
DOI: 10.1051/0004-6361/201833358
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar magnetic cannon targeting the Galactic halo

Abstract: We report the detection of a new Galactic bubble at the interface between the halo and the Galactic disc. We suggest that the nearby Lupus complex and parts of the Ophiuchus complex constitute the denser parts of the structure. This young bubble, 3 Myr old, could be the remnant of a supernova and it expands inside a larger HI loop that has been created by the outflows of the Upper Scorpius OB association. An HI cavity filled with hot X-ray gas is associated with the structure, which is consistent with the Gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Krause et al (2018) verify this by using a 3D hydrodynamic simulation to show that the observed massive star population could reproduce the size and morphology of the observed superbubbles. The presence of soft X-ray emission from the US bubble coupled with the detection of 26 Al confirms that there has been at least one relatively recent ( 1 Myr) supernova from within this subgroup (Robitaille et al 2018;Krause et al 2018).…”
Section: Feedback and Effects On The Local Ismsupporting
confidence: 55%
See 2 more Smart Citations
“…Krause et al (2018) verify this by using a 3D hydrodynamic simulation to show that the observed massive star population could reproduce the size and morphology of the observed superbubbles. The presence of soft X-ray emission from the US bubble coupled with the detection of 26 Al confirms that there has been at least one relatively recent ( 1 Myr) supernova from within this subgroup (Robitaille et al 2018;Krause et al 2018).…”
Section: Feedback and Effects On The Local Ismsupporting
confidence: 55%
“…The interstellar medium surrounding Sco-Cen shows numerous large, loop-like structures and shells that suggest significant interaction between the association and the surrounding medium. They are most clearly seen in Hi observations (e.g., Weaver et al 1977;de Geus 1992;Robitaille et al 2018), with small bubbles centred around US and LCC and a larger bubble encasing the entire association and approximately centred on UCL (de Geus 1992). The total Hi mass of these bubbles has been estimated to be ∼ 5 × 10 5 M and suggested to be composed of gas swept up by stellar winds and supernovae from the progenitor giant molecular cloud that Sco-Cen formed from, as well as the ambient ISM (de Geus 1992).…”
Section: Feedback and Effects On The Local Ismmentioning
confidence: 96%
See 1 more Smart Citation
“…Gaensler et al 2001). At 2.3 GHz in the S-band Polarization All Sky Survey (S-PASS, Carretti et al 2019) Sh2-27 has been identified as a Faraday screen, modulating the polarization angle but not producing polarized emission itself (Robitaille et al 2017(Robitaille et al , 2018Iacobelli et al 2014). In polarization observations at 1.4 GHz, such as GMIMS-HBN, Sh2-27 can be identified as a depolarizing region.…”
Section: Introductionmentioning
confidence: 99%
“…Radiative feedback and winds from newly-formed stars into the nascent cloud material also drive structures on scales of tens or even hundreds of pc, and create sequential episodes of star formation (e.g. Venuti et al 2018) and clear out chimneys and bubbles perpendicular to the galactic plane (Robitaille et al 2018). On smaller scales, how massive stars form remains a topic of intense theoretical work, as models must include the effects of strong radiation pressure and photoevaporation from massive protostars that both limit the available timescale for accretion and may widen existing outflow cavities (Tanaka et al 2017;Rosen et al 2016).…”
Section: Introductionmentioning
confidence: 99%